Sexual politics in modern iran - Afary, Janet (Cambridge University Press, 2009)
Janet Afary is a native of Iran and a leading historian. Her work focuses on gender and sexuality and draws on her experience of growing up in Iran and her involvement with Iranian women of different ages and social strata. These observations, and a wealth of historical documents, form the kernel of this book, which charts the history of the nation's sexual revolution from the nineteenth century to today. What comes across is the extraordinary resilience of the Iranian people, who have drawn on a rich social and cultural heritage to defy the repression and hardship of the Islamist state and its predecessors. It is this resilience, the author concludes, which forms the basis of a sexual revolution taking place in Iran today, one that is promoting reforms in marriage and family laws, and demanding more egalitarian gender and sexual relations